Phenomenological Study: Friends with Benefit (FWB) Decision Making Towards Interpersonal Relationships Through Online Applications - Fuaturosida, Rika; Agung, Yusuf Ratu; Rochim, Edvin Eka Nur; Anshari, Alif Arifzan (Proceedings Conference Psychology and Flourishing Humanity; Vol 1 No 1 (2024): Proceedings Conference on Psychology and Flourishing Humanity, 2025)
Friends with Benefits is a status less relationship between two people who are friends with various motives, including the release of sexuality, the desire to establish FWB, avoiding serious relationships, wanting a simple relationship, and establishing friendship. This study aims to determine the decision making of the friends with benefits relationship on the interpersonal relationship of the perpetrator. The method used is a qualitative research method with a phenomenological approach. The data collection technique used in this research is indepth interviews with participants who have been in friends with benefits relationships. The participants in this study were 2 main subjects and 3 supporting informants. The analysis technique used in this research is Interpretative Phenomenological Analysis (IPA) with the stages of preparing interview transcripts, initial recording, formulating emergent themes, formulating superordinate themes, making patterns of experience between participants and reporting results. Based on the results of the study, it shows that the decision-making pattern of friends with benefits involves a distinctive impression, namely the sexual impression on each participant, the relationship pattern of friends with benefits is described variously, such as friends but intimate, sexual need satisfaction, and relationships limited to having fun. The interpersonal relationship in question is just a friend and the main point of agreement is only sexual activity.